2005
DOI: 10.1002/bmc.570
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance liquid chromatography method development and validation for simultaneous determination of five model compounds, antipyrine, metoprolol, ketoprofen, furosemide and phenol red, as a tool for the standardization of rat in situ intestinal permeability studies using timed wavelength detection

Abstract: A simple, precise, accurate and rugged reversed-phase high-performance liquid chromatography (HPLC) method has been developed and validated for the simultaneous determination of five permeability model compounds, viz. antipyrine, metoprolol, ketoprofen, furosemide and phenol red. The method was intended to standardize rat in situ single-pass intestinal perfusion studies to assess the intestinal permeability of drugs in the market as well as new chemical entities. Optimum resolution was achieved by gradient elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…In addition, the applicability of this method can be extended to other in vitro / in situ / ex vivo permeability assays. Although several studies have reported the simultaneous determination of permeability of marker drugs by HPLC (25)(26)(27)(28)(29), to our knowledge, this is the first report of an HPLC-UV method for the determination of the P-gp substrate VIN concomitantly with the corresponding inhibitor VER, and the four passive permeability markers used in this study. Caco-2 permeability assay -suitability demonstration The formation of a functional single monolayer on polycarbonate inserts is an important feature regarding the mimicking of in vivo conditions in the Caco-2 permeability assay.…”
Section: Hplcmentioning
confidence: 92%
“…In addition, the applicability of this method can be extended to other in vitro / in situ / ex vivo permeability assays. Although several studies have reported the simultaneous determination of permeability of marker drugs by HPLC (25)(26)(27)(28)(29), to our knowledge, this is the first report of an HPLC-UV method for the determination of the P-gp substrate VIN concomitantly with the corresponding inhibitor VER, and the four passive permeability markers used in this study. Caco-2 permeability assay -suitability demonstration The formation of a functional single monolayer on polycarbonate inserts is an important feature regarding the mimicking of in vivo conditions in the Caco-2 permeability assay.…”
Section: Hplcmentioning
confidence: 92%
“…The rat in situ intestinal perfusion is a commonly used technique for evaluating the permeability of drugs and new chemical entities (Kumar et al, 2005;Chawla et al, 2006). Human perfusion studies have shown an excellent correlation with rat in situ intestinal permeability for a variety of compounds (Amidon et al, 1995).…”
Section: In Situ Single Pass Intestinal Permeabilitymentioning
confidence: 99%
“…The rat in situ intestinal perfusion is a commonly used technique for the assessment of permeability of drugs and new chemical entities [5,6] and the functional role of P-gp on the total intestinal transport [7,8]. In this technique the term in situ refers to the methodology in which the animal's blood supply is kept intact, thus the rate of absorption determined by such method would be more consistent with the in vivo situation when compared to other in vitro techniques.…”
Section: Introductionmentioning
confidence: 99%